Man of honour - Ashford, Jane (Sourcebooks Casablanca, 2013)
A snowstorm strands Laura Lindley and Eliot Crenshaw unchaperoned, and her aunt insists they marry. Laura discovers that Eliot has a stunning mistress and doesn't know that he has left her to be with Laura. Laura is in love with her husband, and must unravel a snarl of mistaken motives before she learns that Eliot is as deeply in love as she.